Back Cover: Bending Nanofibers into Nanospirals: Coordination Chemistry as a Tool for Shaping Hydrophobic Assemblies (Chem. Eur. J. 1/2015). Issue 1 (2nd January 2015) - Kossoy, Elizaveta; Weissman, Haim; Rybtchinski, Boris
<x xml:space="preserve">Abstract</x> Synergic action Hydrophobic interactions and coordination chemistry are used to bend columnar stacks into unique nanospirals. The bending aptitudes critically depend on the ability of various metal centers to promote bonding via bridging water ligands. Thus, ZnII coordination chemistry is optimal to make stable nanospirals, CoII gives larger but less stable spirals, whereas NiII affords only straight columnar fibers, providing a convenient "shaping" tool to design complex nanostructures. For more details, see the Full Paper by B. Rybtchinski and co‐workers on page 166 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>